Social Entrepreneurship dalam Pengembangan Eduwisata Kampung Gagot Desa Kutawuluh Kecamatan Purwanegara Kabupaten Banjarnegara - Adelia Putri Auria Azizi; Ageng Widodo (ICODEV: Indonesian Community Development Journal, 2021)
Eduwisata Kampung Gagot is one form of social entrepreneurship activity that relies on the cooperation and participation of the people of Kampung Gagot as an effort to improve the economy and joint welfare. This research aims to describe and analyze the social entrepreneurship process in the development of Kampung Gagot Eduwisata. Researchers use this type of qualitative research with a descriptive approach. The techniques used in data collection are observation, interviews, and documentation. Data analysts use data reduction measures, data presentation, and conclusion withdrawal. The results showed that the process of social entrepreneurship in the development of Eduwisata Kampung Gagot includes, the first is the stage of antecedents, namely starting from determining social missions and identifying social problems as opportunities to be used as a business or business by utilizing existing resources. Second, the stage of entrepreneurial orientation is a strategy used in the development of Eduwisata Kampung Gagot by making the right innovations and risk-taking and does not take issue with competitors to continue to develop and achieve goals. Third, the outcomes stage is the result that wants to be achieved in the social entrepreneurship process in the development of Eduwisata Kampung Gagot, namely the creation of social value by changing mindsets and encouraging people to develop together, create jobs, and achieve prosperity